Intraspecific chemical variability of the leaf essential oil of Juniperus phoenicea subsp. turbinata from Corsica - Rezzi, Serge (2001)
The composition of 50 samples of essential oil of individual plants of Juniperus phoenicea subsp. turbinata from Corsica was investigated by GC, GC-MS and 13C NMR. [alpha]-Pinene, [beta]-phellandrene, [alpha]-terpinyl acetate, [Delta]-3-carene, myrcene and [alpha]-phellandrene were found to be the main constituents. The results were submitted to cluster analysis and discriminant analysis which allowed two groups of essential oils to be distinguished with respect to the content of [alpha]-pinene, [beta]-phellandrene and [alpha]-terpinyl acetate.